2021
DOI: 10.1093/mnras/stab1828
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the LMC-induced sloshing of the Galactic halo

Abstract: A wealth of recent studies have shown that the LMC is likely massive, with a halo mass >1011M⊙. One consequence of having such a nearby and massive neighbour is that the inner Milky Way is expected to be accelerated with respect to our Galaxy’s outskirts (beyond ∼30 kpc). In this work we compile a sample of ∼500 stars with radial velocities in the distant stellar halo, rGC > 50 kpc, to test this hypothesis. These stars span a large fraction of the sky and thus give a global view of the stellar ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 60 publications
1
51
0
Order By: Relevance
“…The LMC has just recently passed the pericentre of its orbit, likely for the first time (e.g., Besla et al 2007), and hence did not yet radialize: its present-day tangential velocity of 310 km s −1 (Gaia Collaboration 2021) at a distance of 50 kpc corresponds to a circularity η = 0.7, using a fiducial Milky Way potential model from McMillan (2017). However, it causes a significant displacement (reflex motion) of the Milky Way centre with respect to its outer parts (Gómez et al 2015;Petersen & Peñarrubia 2020, 2021Erkal et al 2021) and a distortion of its halo (Garavito-Camargo et al 2019Cunningham et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The LMC has just recently passed the pericentre of its orbit, likely for the first time (e.g., Besla et al 2007), and hence did not yet radialize: its present-day tangential velocity of 310 km s −1 (Gaia Collaboration 2021) at a distance of 50 kpc corresponds to a circularity η = 0.7, using a fiducial Milky Way potential model from McMillan (2017). However, it causes a significant displacement (reflex motion) of the Milky Way centre with respect to its outer parts (Gómez et al 2015;Petersen & Peñarrubia 2020, 2021Erkal et al 2021) and a distortion of its halo (Garavito-Camargo et al 2019Cunningham et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…its outskirts, a reflex motion which would create a dipole in the stellar velocity field. Tentative observational evidence for this reflex motion has been recently provided by Petersen & Peñarrubia (2021) and Erkal et al (2021). This reflex motion is expected to be accompanied by a local wake trailing behind the LMC (see, e.g., Garavito-Camargo et al 2019), a phenomenon also tentatively detected by Conroy et al (2021).…”
Section: Introductionmentioning
confidence: 83%
“…The recent passage of a massive accreted satellite complicates the situation further due to the resonances induced in the central DM halo: large transient density and kinematic perturbations (Choi et al 2009) are produced, creating the classical 'conic' wake trailing the satellite (Chandrasekhar 1943) as well as a collective response to the system as a whole (Garavito-Camargo et al 2019) and leading to a temporary change in the concentration of the halo (Wang et al 2020). In fact, it has been recently demonstrated that the LMC induces a reflex motion in the disk/halo of the MW (Gómez et al 2015;Erkal et al 2021;Petersen & Peñarrubia 2021) and a large wake in the halo of the MW (Conroy et al 2021). While modelling the wake and the other homogeneities is beyond the scope of this paper, our work suggests that the errors caused by the use of these spherical parametric models for the potential rival the 30% uncertainty in the virial mass of the MW, and is thus an important source of error to consider.…”
Section: Summary and Discussionmentioning
confidence: 99%